Penguatan Pendidikan Karakter Melalui Keteladanan Guru dan Orang Tua Siswa - Unik Fepriyanti; Abdul Wachid Bambang Suharto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
The purpose of this research is to describe the strengthening of character education through teachers and parents role model at school and at home. This study uses a descriptive qualitative approach. The data were collected through survey and interview by using purposive sampling. The data is analyzed using qualitative data analysis technique. Character education is important in shapping students into individuals who have noble character and good manner. Schools as formal educational institutions are responsible for instilling the values of character education toward their students. Teachers must be the best role models for students in strengthening character education in schools. The parents’ role also determines the success of character education at home. Based on the results of research at MI Ma'arif NU Karanggedang 2 Purbalingga, the values of character education exemplified by teachers and parents are religious character, honesty, tolerance, discipline, social care, creative, independent, care for the environment, love to read, love peace , friendly/ communicative, appreciate achievements, love the homeland, democratic, and responsibility.